Stability-indicating Reversed-phase High-performance Liquid Chromatography Method for the Determination of Fluorometholone in Bulk and Pharmaceutical Formulation - Hemchand, S. (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: A new stability-indicating liquid chromatographic method has been established for the determination of Fluorometholone. Fluorometholone is used for the treatment of eye diseases. Materials and Methods: The Shimadzu Model CBM-20A/20Alite high-performance liquid chromatography (HPLC) system was monitored at detection wavelength 241 nm on isocratic mode with flow rate 0.8 mL/min, and the total run time is 10 min. Chromatographic separation was achieved through Phenomenex Luna C8 column (250 mm × 4.6 mm i.d., 5 μm particle size). The method was validated and stress degradation studies were conducted. Results and Discussion: Fluorometholone has obeyed Beer-Lambert’s law over a concentration range 0.5–100 μg/mL with linear regression equation, y = 70155x + 31667 and correlation coefficient of 0.9996. The limit of detection and limit of quantitation are found to be 0.1617 μg/mL and 0.4502 μg/mL, respectively, and the % RSD in precision, accuracy, and robustness studies was found to be less than 2%. Fluorometholone was found to be highly resistant toward all degradation conditions such as acidic, alkaline, thermal, and oxidation. Conclusions: It is concluded that the proposed reversed-phase HPLC method is accurate, precise, sensitive, and reproducible for the determination of Fluorometholone in pharmaceutical formulations, and the method was validated as per ICH guidelines.